Diagnostics of the formation of the graphic competence of future engineers-educators in the field of digital technologies - Pavlo Ivanovych Koliasa (Kazimierz Wielki University, 2021)
The article analyses the scientific literature on the study of the problem of diagnosing the formation of graphic competence of future engineers-teachers in the field of digital technologies. Based on the analysis, the criteria for the formation of components of graphic competence (value-motivational, activity criteria, personal-creative and communicative-organizational criteria) are determined. An important aspect of the study is to determine the levels of graphic competence of future engineers-educators in the field of digital technologies, which we defined as: intuitive, reproductive, exploratory and creative, determined by the criteria and indicators of certain components